Exercise catalogue for biathlon shooting - Sattlecker, G.; Edfelder, J.; Gressenbauer, C. (University of Salzburg/IBU, 2018)
Introduction Shooting is a crucial discipline in biathlon. Therefore, shooting technique plays a significant role in successful performance. The differential learning approach ac-cording to Schöllhorn (1999) is a modern tool used to improve and optimize technical skills as well as coordination. This method is based on the principle of dynamic system theory (Janssen et al., 1996; Thelen & Smith, 1993): It considers human beings to be self-organizing systems. This means that the experience of different technical stimuli leads to a earning process. Consequently, an individual and optimal movement solution can be generated. In order to achieve these adaptations, variable conditions and differing complexity are required in the training schedule. Variations occur by deliberately creating instability in connection with a specific technique. As a result, the athlete`s attention is drawn to the particular technical elements of the movement. By counter-acting this instability, the athlete experiences differences. By executing a variety of movements, the athlete expands his/her knowledge of possible solutions for the movement technique. This development effects technical progress in high level sports. Unlike stereotypical types of training, variation in the training schedule creates an adaptable technique. Only if alternatives are offered can an athlete learn to distinguish sensitively between possible technique solutions and "errors". Thus, individual optimum techniques can be achieved. Since the differential learning method forces the athlete to react directly according to his/her surroundings, he/she learns to respond properly, even to extreme conditions. These adaptations should also take place rapidly and automatically under difficult conditions (such as during competitions). Therefore, this type of technique training also challenges athletes with a highly developed technical level.